Ultrasound Elastography - Dietrich, Christoph F. (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
The comparison between methods, evaluation of portal hypertension and many other questions are still open issues in liver elastography. New elastographic applications are under evaluation and close to being used in clinical practice. Strain imaging has been incorporated into many disciplines and EFSUMB guidelines are under preparation. More research is necessary for improved evidence for clinical applications in daily practice. The Special Issue published papers on recent advances in development and application of Ultrasound Elastography.